2001
DOI: 10.1016/s0306-5456(00)00199-6
|View full text |Cite
|
Sign up to set email alerts
|

Combination of cervical interleukin-6 and -8, phosphorylated insulin-like growth factor-binding protein-1 and transvaginal cervical ultrasonography in assessment of the risk of preterm birth

Abstract: Objective To determine the value of combinations of cervical interleukin-6 (IL-6), cervical interleukin-8 (IL-8), the phosphorylated isoform of insulin-like growth-factor binding protein-1 (IGFBP-1), and cervical ultrasonography in the prediction of preterm birth. Design Prospective follow up.Setting Oulu University Hospital maternity clinic from February 1997 to July 1998. Population Women with singleton pregnancies (n 77), referred from outpatient clinics at 22±32 weeks of gestation with symptoms (uterine co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 28 publications
0
33
0
3
Order By: Relevance
“…We found that zinc supplementation during pregnancy significantly attenuated LPS-induced upregulation of TNF-a and IL-1b in placenta. Increasing evidence demonstrates that IL-6 and IL-8 are associated with preterm delivery (36,37). An earlier report showed that treatment of murine decidual explants with LPS resulted in significant increases in IL-6 (38).…”
Section: Discussionmentioning
confidence: 99%
“…We found that zinc supplementation during pregnancy significantly attenuated LPS-induced upregulation of TNF-a and IL-1b in placenta. Increasing evidence demonstrates that IL-6 and IL-8 are associated with preterm delivery (36,37). An earlier report showed that treatment of murine decidual explants with LPS resulted in significant increases in IL-6 (38).…”
Section: Discussionmentioning
confidence: 99%
“…231 For symptomatic women, one study reported spontaneous preterm birth within 24 hours, 240 five studies within 48 hours 120,223,225,237,239 and four studies reported birth within 5-7 days of testing, 226,236,238,241 while the remainder reported birth before 35-37 weeks' gestation. 90,103,218,224,[227][228][229][230]233,235 Accuracy of IL-6 in asymptomatic women For (Figure 43). For predicting spontaneous preterm birth before 37 weeks' gestation, a single amniotic fluid IL-6 measurement had an LR+ of 1.91 (95% CI 0.99-3.67) and LR-of 0.95 (95% CI 0.90-1.00) ( Figure 43).…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
“…103 There were 12 studies evaluating the amniotic level of IL-6, two in asymptomatic women 220,222 and ten in symptomatic women, 120,218,[223][224][225][226][227][228][229][230] as a predictor for spontaneous preterm birth. There were ten studies evaluating cervical IL-6, three in asymptomatic women 103,221,231 and seven in symptomatic women 90,103,[232][233][234][235][236] as a predictor of spontaneous preterm birth in women. One study evaluated serial testing of cervical IL-6 in asymptomatic women.…”
Section: Study Characteristics and Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…4 Many chorion/decidual products have been evaluated as markers for PTD. [4][5][6][7][8][9][10] In most studies, the performance of potential marker molecules has been evaluated among women with uterine contractions or preterm labour during the late-second trimester or third trimester.…”
Section: Introductionmentioning
confidence: 99%